2010
DOI: 10.1039/c003189e
|View full text |Cite
|
Sign up to set email alerts
|

DNP enhanced NMR using a high-power 94 GHz microwave source: a study of the TEMPOL radical in toluene

Abstract: DNP enhanced (1)H NMR at 143 MHz in toluene is investigated using an NMR spectrometer coupled with a modified EPR spectrometer operating at 94 GHz and TEMPOL as the polarisation agent. A 100 W microwave amplifier was incorporated into the output stage of the EPR instrument so that high microwave powers could be delivered to the probe in either CW or pulsed mode. The maximum enhancement for the ring protons increases from approximately -16 for a 5 mM TEMPOL solution to approximately -50 for a 20 mM solution at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 25 publications
1
39
1
Order By: Relevance
“…The interaction and relaxation parameters used for these calculations are given in Table 1 1;e effects the populations by bringing them to the ratios given in Eq. (34). Changes in the values of T À1 2n ð6 T À1 2e Þ and A z ((x n ) had no observable effects on the results shown here.…”
Section: Simulations Of Polarization Enhancementsmentioning
confidence: 59%
See 1 more Smart Citation
“…The interaction and relaxation parameters used for these calculations are given in Table 1 1;e effects the populations by bringing them to the ratios given in Eq. (34). Changes in the values of T À1 2n ð6 T À1 2e Þ and A z ((x n ) had no observable effects on the results shown here.…”
Section: Simulations Of Polarization Enhancementsmentioning
confidence: 59%
“…In the case of solution DNP at high fields, recent experimental results demonstrate that for high microwave powers one can achieve NMR signals that are higher than predicted theoretically [33][34][35]. For radicals mixed in frozen solutions, it has been shown that for systems in which the SE is the only DNP mechanism the enhancements are quite low [36,37].…”
Section: Introductionmentioning
confidence: 98%
“…However, when high power, high-frequency microwave sources became available, Griffin and coworkers demonstrated polarization transfer mechanisms that scale more efficiently with B 0 , such as the cross effect and the Overhauser effect in insulating solids [911]. DNP via the Overhauser effect in liquids involves stochastic interactions between the electron spins of stable radicals and the nuclei of interest that are either dominated by dipolar [1216] or scalar interactions [7,14,17], and can theoretically enable significant polarization enhancements even at field strengths of interest for solution-state analytical NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty in predicting coupling factors, which depend on the detailed atomistic interactions between the polarizer and the solvent as well as system-specific correlation functions of molecular motion, any chemical variations in the polarizer molecule or the solvent might lead to large changes in the DNP efficiency. Recently, DNP with nitroxides in non-aqueous solvents, such as toluene 16,17 or benzene, 18 has been reconsidered by taking advantage of instrumental developments at different magnetic fields and progress in analysis. These non-polar solvents might be particularly attractive to host more complex organic polarizers and have the great advantage of low dielectric losses, which attenuate microwave heating.…”
mentioning
confidence: 99%